Clinical features of COVID-19 infection in patients with myasthenia gravis: a real-world retrospective study - Li, Hui-Ning; Xu, Xiao-Na; Qin, Ying-Hui; Liu, Rui; Guo, Wen-Yue; Huang, Xiao-Yu; Fan, Mo-Li; Zhang, Lin-Jie; Qi, Yuan; Zhang, Chao; Yang, Li; Shi, Fu-Dong; et al. (Frontiers in Public Health, 2024)
Objective We investigated the risk factors associated with severe or critical Coronavirus disease 2019 (COVID-19) infection due to the Omicron variant in patients with myasthenia gravis (MG) and determined the potential effect of COVID-19 on myasthenic exacerbation during the Omicron pandemic. Methods This retrospective study included 287 patients with MG in Tianjin, China. Clinical data of the patients were collected using electronic questionnaires, databases, and clinical records. Results The overall infection rate was 84.7%. Advanced age, comorbidities, generalized phenotype, and MG instability were drivers of COVID-19 severity, and post-COVID-19 myasthenic exacerbation. The concurrent use of a steroid-sparing agent did not affect COVID-19 susceptibility or severity. It did lower the risk of myasthenic exacerbation after COVID-19 infection. Patients with severe COVID-19 experienced myasthenic exacerbation earlier than patients with non-severe infection (p < 0.001). The severity of COVID-19 (Hazards Ratio = 3.04, 95% CI: 1.41–6.54, p = 0.004) and the clinical phenotype (Hazards Ratio = 3.29, 95% CI: 1.63–6.63, p < 0.001) emerged as independent risk factors for early MG exacerbation. Conclusion Generally, patients with MG appear to be susceptible to the Omicron strains. Immunotherapy for MG did not increase COVID-19 susceptibility or severity. We do not advocate an immediate cessation of ongoing immunosuppressive treatments once a COVID-19 infection is diagnosed. Instead, a judicious evaluation of the risks and benefits, tailored to each individual, is recommended.